Використання високобілкової рослинної сировини у технології хлібобулочних виробів спеціального дієтичного споживання. - Черниш, Людмила Миколаївна (My University, 2018)
Робота присвячена використанню високобілкової рослинної сировини у хлібопеченні з метою підвищення біологічної цінності хлібобулочних виробів. Науково обґрунтовано доцільність використання ізолятів соєвого, горохового і рисового білків у технології хлібопекарського виробництва та розроблення хлібобулочних виробів з поліпшеним амінокислотним складом. Запропоновано сумісне внесення ізолятів рослинних білків як білкових збагачувачів та сухої пшеничної клейковини як технологічного поліпшувача. На підставі досліджень розроблено хлібобулочні вироби спеціального дієтичного споживання для збагачення раціону людей IV групи інтенсивності праці та спортсменів силових видів спорту повноцінним рослинним білком. Визначено, що внесення ВРС сприяє формуванню пружно-еластичних і в’язко-пластичних властивостей тіста. Експериментально доведено вплив співвідношення фракцій білків ВРС у зв’язуванні ними води та формуванні структурно-механічних властивостей тіста. Досліджено вплив ВРС на показники технологічного процесу і якість хліба. Рекомендовано способи тістоприготування виробів, підібрано технологічні режими. Встановлено, що вироби з ВРС краще зберігають свіжість внаслідок збільшення вмісту зв’язаної вологи, внесення білкових збагачувачів зумовлює покращення перетравлюваності виробів. Розраховано хімічний склад, харчову та енергетичну цінності хлібобулочних виробів. Доведено, що вміст білка в порівнянні з традиційним пшеничним хлібом у досліджуваних зразках значно зростає. Збалансування хімічного складу розроблених виробів і підвищення засвоюваності їх білків дасть можливість повністю задовольнити потребу у рослинних білках споживачів IV групи інтенсивності праці та спортсменів силових видів спорту у разі споживання нормативної кількості хліба (277 г/добу). The work is devoted to the use of high-protein vegetable raw materials (HI-PRO VRM) in bakery in order to increase the biological value of bakery products. We scientifi-cally substantiated the feasibility of using soy, pea and rice protein isolates (SBI, PPI, RPI) in bakery technology and development of bakery products with an improved amino acid composition. To produce the high quality products, balanced by the protein component, we proposed to jointly introduce isolates of vegetable proteins as protein enrichers and dry wheat gluten (DWG) as a technological enhancer in the following ratio. Based on the re-searches, we developed bakery products of a special dietary consumption to enrich the diet of people of the IV group of work intensity and athletes of power sports with a complete vegetable protein. We have determined that HI-PRO VRM have a high water absorption and fat-retention capacity. The introduction of HI-PRO VRM contributes to the formation of vis-co-elastic and elasto-plastic properties of the dough. We established that due to the for-mation of HI-PRO VRM protein complexes with the flour components, the amount of glu-ten is reduced, as well as there is an increase in hydration capacity and a decrease in its elasticity. We experimentally and theoretically proved the influence of the ratio of HI-PRO VRM protein fractions in water binding and forming the structural and mechanical proper-ties of the dough, which made it possible to propose a calculated coefficient of water-absorbing ability of the dough with HI-PRO VRM: SBI – 2.2; PPI – 1.5; RPI – 0.9; DWG – 1.2. We carried out a comparative analysis of the amino acid composition of bread pro-teins and calculated the amino acid rate with the determined dosages. We studied the HI-PRO VRM influence on the technological process parameters and the quality of bread. We recommended the methods of dough preparation and selected the technological modes. Based on the research results, we developed the formulations and technological in-structions for "High protein" bread - DWG/SBI, "Protein with peanut isolate" bread - DWG/PPI, "Protein with rice isolate" bread - DWG/RPI, which were approved by the as-sociation of baking industry enterprises "Ukrkhlibprom". We established that the developed products preserve freshness better as a result of an increase in the content of bound moisture due to a decrease in the starch retrigration. The HI-PRO VRM introduction into the products leads to an increase in the products digesti-bility. We calculated the chemical composition, food and energy values of bakery products. We proved that the protein content increased significantly in comparison with the tradi-tional wheat bread in the studied samples. We established that the ratio of proteins and carbohydrates became closer to the physiological norm at the almost unaltered energy val-ue. We calculated the amino acid rate of lysine, utilitarian coefficient and the amount of digestible protein. We proved that balancing the chemical composition of the developed products and increasing the assimilation of their proteins would enable to fully satisfy the need for vegetable proteins in the IV group of work intensity. The proposed technical solutions are confirmed by the patent of Ukraine on utility model No. 106058 "High-Protein Bakery Product", the patent of Ukraine on utility model No. 166563 "Bread with High Content of Vegetable Protein". The developed formulations of bakery products were tested in production conditions during the release of experimental lots and introduced into production at the Ukrainian en-terprises.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; технологія; хліб; білок; амінокислоти; біологічна цінність; ізолят; соя; горох; рис; суха пшенична клейковина; харчування; technology; bread; protein; amino acids; biological value; isolate; soy; pea; rice; dry wheat gluten; food